The Legal Framework for Crimes Related to Augmented and Virtual Reality - Asfoor, Nidaa Mohamed; Talib, Zainab Kadhim (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Augmented Reality (AR) and Virtual Reality (VR) era are growing notable immersive environments, collectively contributing to the burgeoning Metaverse. While providing big societal and monetary blessings, these structures also present novel avenues for crook interest. Aims: This studies examines the adequacy and applicability of existing prison frameworks, generally countrywide criminal statutes and international cybercrime conventions, to deal with crimes devoted interior or facilitated with the useful resource of AR and VR environments. Method: Employing a qualitative, doctrinal criminal analysis approach, the study scrutinizes key stressful situations consisting of the definition of damage in digital spaces, the felony repute of virtual belongings, jurisdictional complexities bobbing up from the without boundaries nature of these technology, issues in accumulating admissible digital evidence, and issues surrounding individual anonymity and avatar attribution. Findings: Findings mean huge gaps and ambiguities internal contemporary jail structures. Existing legal suggestions, regularly designed for tangible harms or earlier sorts of virtual interplay, conflict to efficiently embody nuanced offenses like virtual attack, harassment, or theft of virtual property. Furthermore, large procedural hurdles related to jurisdiction, proof series, and offender identification avoid powerful law enforcement. Result: The studies concludes that relying entirely on analogical interpretations of present legal guidelines is insufficient and doubtlessly useless. Novelty: It underscores the urgent need for taken into consideration prison version, whether via legislative reform, delicate judicial interpretation, or improved worldwide cooperation, to make certain consumer protection, maintain consider, and foster accountable innovation within immersive digital realms. Impact: This study contributes to cyberlaw scholarship by imparting a synthesized analysis of criminal law challenges specific to modern AR/VR and gives insights for policymakers, legal practitioners, and era developers navigating this evolving panorama. Highlights: Existing criminal statutes are ambiguous and often inapplicable to immersive AR/VR offences. Significant jurisdictional and evidentiary hurdles hinder prosecution across virtual borders. The paper proposes an adaptive, technology‑neutral legal framework that balances innovation with user protection. Keywords: Augmented Reality, Virtual Reality, Cybercrime Law, Jurisdiction, Digital Evidence